Effects of Chronic and Acute Intranasal Oxytocin Treatments on Temporary Social Separation in Adult Titi Monkeys (Plecturocebus cupreus) - Arias del Razo, Rocío; Velasco Vazquez, Maria de Lourdes; Turcanu, Petru; Legrand, Mathieu; Lau, Allison R.; Weinstein, Tamara A. R.; Goetze, Leana R.; Bales, Karen L. (Frontiers in Behavioral Neuroscience, 2022)
In socially monogamous titi monkeys, involuntary separation from a pair mate can produce behavioral distress and increased cortisol production. The neuropeptide oxytocin (OXT) is thought to play an important role in the separation response of pair-bonded species. Previous studies from our lab have shown that chronic intranasal oxytocin (IN OXT) during development can have long-term effects on adult social behavior. In the current study, we examined the chronic and acute effects of IN OXT or Saline (SAL) on the subjects’ response to a brief separation from their pair mate. Subjects with a history of chronic IN OXT or SAL treatment during development received a single dose of OXT or SAL as adults 30 minutes before being separated from their pair mate. Chronic treatment consisted of a daily dose of IN OXT (0.8 IU/kg) or SAL (control) from 12 to 18 months of age. Subjects (N=29) were introduced to a pair mate at 30 months of age. After the pairs had cohabitated for 5 months, pairs underwent two “Brief Separation” (OXT and SAL) and two “Non-Separation” (OXT and SAL) test sessions. Vocalizations and locomotion were measured as behavioral indices of agitation or distress during the Brief Separation and Non-Separation periods (30 minutes each). We collected blood samples after the Brief Separation and Non-Separation periods to measure cortisol levels. Our results showed subjects treated with chronic OXT had a reduction in long call and peep vocalizations compared to subjects treated with chronic SAL. Subjects treated with chronic SAL and acute OXT produced more peeps and long calls compared to animals treated with acute SAL; however, patterns in this response depended on sex. Cortisol and locomotion were significantly higher during the Brief Separation period compared to the Non-Separation period; however, we did not find any treatment or sex effects. We conclude that chronic IN OXT given during development blunts the separation response, while acute OXT in chronic SAL subjects had sexually dimorphic effects, which could reflect increased partner seeking behaviors in males and increased anxiety in females.